2021
DOI: 10.54203/scil.2021.wvj9
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Characteristics, Serum Metabolites, and Oxidative Status in Female Guinea Pigs (Cavia porcellus) Fed with Ethanolic Extract of Dichrostachys glomerata Fruit

Abstract: Dichrostachys glomerata (D. glomerata) is an aromatic plant which is used as a spice in cooking and Cameroonian traditional medicine to treat infertility in men. This work was designed to highlight the effects of the ethanolic extract of D. glomerata on oxidative status, serum metabolites and reproductive characteristics in female guinea pigs (Cavia porcellus). A total of 48 primiparous female guinea pigs, aged 4 months old with the body weight of 400 ± 10 g, were divided into four groups with two replications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The improvement in pig diarrhoea was good, but the data difference was not significant. This was mainly due to the lower occurrence of adverse reactions such as diarrhoea during the later growth process of pigs due to the improvement of their body mass and the stability of environmental conditions (Djuissi et al 2021;Guo et al 2021). Plant sterols in pigs can inhibit the absorption of animal cholesterol, thereby achieving its degradation and metabolism, regulating the permeability and stability of liposomes, and improving the gastrointestinal function and nutrient absorption ability of pigs, which has a promoting effect on their growth (Bhattacharyya 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in pig diarrhoea was good, but the data difference was not significant. This was mainly due to the lower occurrence of adverse reactions such as diarrhoea during the later growth process of pigs due to the improvement of their body mass and the stability of environmental conditions (Djuissi et al 2021;Guo et al 2021). Plant sterols in pigs can inhibit the absorption of animal cholesterol, thereby achieving its degradation and metabolism, regulating the permeability and stability of liposomes, and improving the gastrointestinal function and nutrient absorption ability of pigs, which has a promoting effect on their growth (Bhattacharyya 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The fruit is a dried pod commonly used as a spice in " Nah poh ", a traditional Cameroonian soup [ 7 ]. D. glomerata have been found to contain various components such as flavonoids, phenolic compounds, alkaloids, tannins, saponins, and terpenoids [ 8 ]. Recent studies have shown that D. glomerata has antioxidant activity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%